Analysis of over-the-counter medicines use among nursing students - Mlinar, Suzana; Rašković Malnaršič, Rosanda (Vojnosanitetski pregled, 2015)
Background/Aim. The use of over-the-counter (OTC) medication is widespread among the adult and student populations in Slovenia. The aim of the study was to analyse the prevalence of OTC medicines use among nursing students with respect to sociodemographic characteristics. Methods. A total of 241 nursing students in the Faculty of Health Sciences, Ljubljana, were included in the cross-sectional study. A questionnaire was created for the purposes of the study. Statistical analysis was performed with SPSS 20. Descriptive statistics, t-test and the contingency coefficient were calculated. Statistical significance was set at the p-value of < 0.05. Results. The study showed that the use of prescription drugs was significantly higher in women (p = 0.029), students living in rural areas (p = 0.005) and students who described themselves as being of bad health (p = 0.008). At the same time, a third of the respondents had been taking one OTC medicine within the last month; those taking several prescription drugs commonly administered several over-the-counter medicines (p = 0.027). Women used OTC medicines to treat pain and fever (p = 0.001), respiratory issues (p = 0.015), and fungal infections (p < 0.000) more often than men. OTC medicines were also used to treat minor mental health issues by a higher proportion of respondents over 21 years of age (p = 0.005) and women (p < 0.000), while over-the-counter medicines for treating skin conditions were more frequently used in rural areas (p = 0.006). Conclusion. Nursing students tend to use OTC medicines on their own accord, receiving instructions for safe use with their purchase, which points to adequate promotion of safe use of medications in Slovenia. Men's assessment of their personal health tends to be better than that of women, who also use medication more frequently. A connection between poor health and a higher incidence of the use of OTC medicines was established. The use of OTC medicines to treat minor mental health issues increased with age and was more typical of women. The results obtained demonstrate the importance of personal control over the safe use of medicines, motivation for personal good health and a healthy lifestyle.
Keywords: nonprescription drugs; questionnaires; students; medical staff; socioeconomic factors; decision making